Bimbingan dan Konseling Islam dengan Teknik Token Economy dalam Membentuk Disiplin Shalat pada Anak di Sidoarjo (Jurnal Bimbingan dan Konseling Islam, 2018)
In this study the researcher uses the token economy technique in which this technique is an effort to provide assistance to clients, where targeted behaviors (disciplining prayer) are given reinforcement derived from the client extrinsic in the form of a token (Allah's lafadz sticker), and the token can be used by clients to be exchanged for various expected strengths in accordance with the initial contract that has been made with the counselor. In addition, counselors also provide positive confirmation that is to express words of praise to clients if they are able to carry out a contract of behavior well. In this study it was concluded that the previous client was not disciplined in performing prayers marked by the difficulty when ordered to pray, stalling for time, never praying together, rarely isha prayer and even prayer for no prayers. By using this token economy technique, the final result of the Islamic Guidance and Counseling process was declared to be quite successful with a 66.6% process in which the results can be seen from the changes in client attitudes or behavior that are not good starting to be better, namely the implementation and safeguarding client prayers is increasing after getting BKI with the token economy technique.